Wage differentials based on trade and globalisation. - Chen, Constance RuYun. (2010)
The paper investigates the effect of trade and globalisation on wage differentials in Singapore, testing the hypothesis that increased economic integration has attributed to the wage gap between workers of different skill levels. Overall, the findings show that, contrary to past research, increase in trade has only had a modest effect on wages in all industries. With the examination of some indicators of globalisation, our paper concludes that globalisation is the key factor in causing wage differentials. The paper also provides an in-depth explanation of how the different indicators affect workers of different skill levels in the manufacturing and services sectors.